An Analysis of Task-Based Language Teaching (TBLT) Approach Used by The Teacher in Writing Skill at Bina Cita Mandiri (BCM) Course & Counseling - Aisyah, Risfa Nur; Asi, Natalina; Ristati, Ristati (PROJECT (Professional Journal of English Education), 2025)
Task-based language teaching (TBLT) is a communicative approach that views language as a tool for communication. Learners acquire language by completing meaningful, well-structured tasks. The research aimed to examine how the teacher at BCM Course & Counseling applies the TBLT approach to teaching writing and the challenges faced in using this method. The researcher used descriptive qualitative method. Three instruments were utilized observation, interview, and documentation for collecting the data. The subject was the English teacher at 5th Grade in BCM Course & Counseling, Palangka Raya. The researcher obtained the teacher at Bina Cita Mandiri (BCM) Course & Counseling utilizes the TBLT approach by integrating a series of well-designed tasks into the English writing curriculum, which align with real-world activities. Tasks such as arranging sentences, translating words, and filling in blanks worksheets task from online resources like iSL Collective and Live Worksheet. Group discussions form a core part of the TBLT approach at BCM. Students are divided into small groups, and each group works collaboratively on the assigned writing tasks. The problems that the researcher found while observing and interviewing the teachers. There were students' cognitive abilities, difference in curricula, student attendance, motivation, and limited practice opportunities.